30 Role of post-operative radiotherapy following neurosurgical resection of brain metastases – 5-year single centre retrospective analysis - Lauren Best; Laura Palles-Clark; Sara Walters; Rebecca John; James Powell; Jillian Maclean; Kathrin Whitehouse; George Eralil; Najmus Sahar Iqbal (Neuro-Oncology, 2026)
Abstract Introduction Surgical resection of brain metastases offers reduced local recurrence, improved functional independence, and improved overall survival. NICE does not recommend adjuvant stereotactic radiosurgery (SRS) or whole brain radiotherapy (WBRT) following complete surgical resection of brain metastasis. Method 140 patients were identified from the South Wales Neuro-Oncology MDT between 2018 and 2023 who underwent neurosurgical resection for brain metastases. Demographics including primary cancer, presence of residual disease, and adjuvant treatments were recorded from electronic patient records. Radiological progression was assessed, including date, location of recurrence, and subsequent management. Primary outcomes were overall survival (OS) and time to progression, analysed using Kaplan-Meier curves with log-rank testing for statistical significance. Results Mean age was 60.19 years (range 28–81); 58.57% were female. The most common primary tumours were lung (41.43%), melanoma (19.29%), and breast (15.14%). Radiologically confirmed residual disease was present in 24 patients and absent in 34, with the remainder unknown. 37 patients received adjuvant SRS to the surgical cavity, 9 underwent WBRT), and 94 received no adjuvant radiotherapy. Median overall OS was 9.0 months (95% CI: 6.5–11.5). Median OS was significantly higher in patients receiving SRS (24.0 months) and WBRT (22.0 months) compared to no adjuvant radiotherapy (6.0 months) (p = 0.005). Local recurrence at the surgical site occurred in 80 patients, of whom 9 received SRS, 14 underwent WBRT, and 1 received partial radiotherapy. Conclusions Adjuvant radiotherapy to the surgical cavity is associated with substantially improved survival compared to observation alone. Both SRS and WBRT conferred comparable benefit over no treatment. However, due to toxicities of WBRT, SRS may be a preferred option in these patients. These findings are limited by retrospective design and patient selection bias and warrant prospective randomised evaluation.